2019
DOI: 10.2147/cmar.s213882
|View full text |Cite
|
Sign up to set email alerts
|

<p>Feasibility and safety of neoadjuvant laparoscopic hyperthermic intraperitoneal chemotherapy in patients with advanced stage ovarian cancer: a single-center experience</p>

Abstract: For patients with advanced ovarian cancer, neoadjuvant chemotherapy (NACT) can significantly increase the rate of optimal cytoreduction. However, this does not translate into a survival benefit. The aim of this study was to investigate the feasibility and effect of neoadjuvant laparoscopic hyperthermic intraperitoneal chemotherapy (NLHIPEC). Methods: Between March 2016 and February 2018, 14 patients with advanced ovarian cancer who were not candidates for optimal cytoreduction via primary debulking surgery (PD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 38 publications
1
18
0
Order By: Relevance
“…In addition, MIS cytoreductive surgery combined with HIPEC was associated with reduced interval to chemotherapy [ 22 ]. In addition, similar to our results, in a retrospective study of 14 patients with EOC who underwent MIS HIPEC following NACT, no post-operative complications occurred and the majority of patients (71.4%) had R0 resection [ 23 ]. Our data builds on these prior studies supporting that in women with advanced EOC, HIPEC at the time of MIS IDS is feasible and with low rates of post-operative complications.…”
Section: Discussionsupporting
confidence: 89%
“…In addition, MIS cytoreductive surgery combined with HIPEC was associated with reduced interval to chemotherapy [ 22 ]. In addition, similar to our results, in a retrospective study of 14 patients with EOC who underwent MIS HIPEC following NACT, no post-operative complications occurred and the majority of patients (71.4%) had R0 resection [ 23 ]. Our data builds on these prior studies supporting that in women with advanced EOC, HIPEC at the time of MIS IDS is feasible and with low rates of post-operative complications.…”
Section: Discussionsupporting
confidence: 89%
“…The aim of this study was to investigate the feasibility of a more comprehensive and relatively aggressive treatment regimen in the management of locally advanced GC. The efficacy of HIPEC as a prophylaxis against PC primary to disease progression or secondary to surgical trauma has been investigated and supported in previous literature [14,[19][20][21][22] . The role of chemotherapy in the pre-surgical setting with the main goals of tumor downsizing and down-staging has also been thoroughly investigated and acclaimed over the past few decades [27][28][29][30] .…”
Section: Discussionmentioning
confidence: 80%
“…In a study by Coccolini et al, prophylactic HIPEC associated to NAC increased the DFS and OS in patients with AGC without carcinomatosis [19] . Nevertheless, there have been more reports about the combination of NAC followed by HIPEC improving the survival rates in ovarian cancer [20][21] . On the other hand, there have been fewer reports about the efficacy of laparoscopic HIPEC (L-HIPEC): in a report by Yonemura et al, L-HIPEC combined with intraperitoneal chemotherapy could decrease PCI index before cytoreductive procedures [22] .…”
Section: Introductionmentioning
confidence: 99%
“…This recommendation is based on the evidence that the synergistic effect of hyperthermia and cisplatin can be dramatically increased at 42°C [10]. Data from clinical research also confirmed the safety and effectiveness of HIPEC at 43°C [31][32][33][34]. In general, the properties of biological tissues, the toxicity of drugs and their mutual influences change under hyperthermic conditions; some of the changes are temperature dependent [35].…”
Section: Hipec-related Aes Are Summarized In Supplementarymentioning
confidence: 99%